Eksistensi Organisasi Karang Taruna Tomini Raya Di Desa Kayubulan Kecamatan Batudaa Pantai Kabupaten Gorontalo - Iloponu, Ristiwinarty; Kadir, Jusrin; Antu, Yahya (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This study was conducted to determine and describe the existence of the Tomini Raya youth organization in Kayubulan village, Batudaa Pantai sub-district, Gorontalo regency. This study uses a descriptive type with a qualitative approach. Data collection was carried out through observation and interviews using interview guidelines submitted to a number of informants with the focus of the study being participation, budget, and management of administrators.The results of the study showed that the existence in terms of participation was still not optimal because many members of the youth organization were busy with their respective activities and the lack of concern from members for the youth organization. However, on the other hand, member participation in village activities, especially approaching August 17 and religious ritual moments such as the Prophet's Birthday and Ramadan, is quite good and active, although not all members are active, so the program does not run, including youth activities initiated by the village government. From the aspect of the budget, it is still very minimal or even non-existent, so many programs that were planned at the beginning do not run. The budget for activities is usually the result of a joint effort by several members and donors. From the aspect of management, the management is less active. Another thing is that there are no programs running in Kayubulan village since 2023. The programs implemented are village programs with funding from the village government. The village government is considered to be too involved in the management of the youth organization so that management is not optimal. The existence of the youth organization currently cannot be improved when viewed from the form of management of the existing management.It is recommended that the existence of youth organization be increased through increased member participation, good budget management, and good organizational management so that the Tomini Raya youth organization runs optimally.